Longitudinal study of Orthohantavirus hantanense in Apodemus agrarius and disease risk assessment in the Republic of Korea during 2000–2019 - Terry A. Klein; Kyungmin Park; Shivani Rajoriya; Heung Chul Kim; Jongwoo Kim; Seung-Ho Lee; Se Hun Gu; William J. Sames; Monica L. O’Guinn; Michael J. Turell; Yu-Jin Kim; Jieun Park; et al. (Scientific Reports)
Abstract Orthohantavirus hantanense (HTNV) is a zoonotic pathogen transmitted by rodents and the causative agent of hemorrhagic fever with renal syndrome (HFRS) in East Asia. Long-term reservoir population ecology studies have enhanced our understanding of hantavirus infection patterns and support disease risk assessments critical for military and civilian populations in HTNV high-risk areas. Here, we evaluated fluctuations in the population dynamics of Apodemus agrarius, the primary reservoir of HTNV, assessed hantavirus seroprevalence, and conducted a descriptive analysis of HFRS disease risks in the Republic of Korea (ROK). From 2000 to 2019, a total of 12,476 small mammals representing 15 species were captured across locations spanning northern to southern regions. A. agrarius was the most frequently collected species in the ROK, with juvenile populations peaking during the late fall/winter seasons. A high proportion of A. agrarius captured at military installations/training sites near the Demilitarized Zone tested seropositive for immunoglobulin G antibodies against HTNV, whereas none of those trapped in Jeollanam Province were seropositive. Risk assessment identified high-risk HFRS zones in northern Gyeonggi and Gangwon Provinces. This study provides important insights for forecasting heightened viral transmission risks to humans and implementing targeted mitigation strategies in HFRS high-risk regions of the ROK.